Immunosuppression in uterus transplantation: from transplant to delivery. (2nd January 2023) - D'Amico, Giuseppe; Del Prete, Luca; Eghtesad, Bijan; Hashimoto, Koji; Miller, Charles; Tzakis, Andreas; Quintini, Cristiano; Falcone, Tommaso
ABSTRACT: Introduction: Uterus transplantation introduces unique challenges regarding immunosuppression, including the effects of immunosuppressive drugs on the fetus and graft rejection during pregnancy. Although immunosuppressive regimens are based on protocols used after solid organ transplantation, in recipients of uterus grafts, the physician must consider therapy modifications based on the phase of the transplant, from the intra-operative period through to delivery. Areas covered: This review discusses the current immunosuppressive rationale in uterus transplantation, focusing on the therapy in each phase of the transplant. The authors present an overview of the already approved immunosuppressive medications for solid organ transplantation, their application in uterus transplant prior to pregnancy, during pregnancy and as rejection treatment. Expert opinion: Most medications used for uterus transplant are adopted from solid organ transplantation experience, especially kidney transplantation, and rejection is treated in standard fashion. Research is needed to clarify the drugs' effects on fetal and neonatal well-being and to develop new medications to achieve better tolerance. Early markers of uterus graft rejection need to be identified, and prior rejection episodes should no longer be a cause to remove the graft during delivery in a recipient who wants a further pregnancy.